Entrepreneurship in Transitional Economies - Lasserre, Philippe (Chinese Management Studies: Volume 9, Issue 2, 2015)
It is believed that transitional economies represent a very unique research context. There are abundant opportunities for entrepreneurship studies facing the transitional economies. This issue tries to make explorations in such aspect. The six manuscripts in this issue cover three topics: relationship within the context of entrepreneurship, entrepreneurship in history, and entrepreneurship in specific industries. With deep quality and quantity study, they show some interesting conclusions about strategy, organizational behavior, management in entrepreneurship study. Generally, this special issue will bring some ideas about the research domains and opportunities of entrepreneurship in transitional economies